The Cascade [1,5]-Hydride Shift/Intramolecular C(sp3)–H Activation: A Powerful Approach to the Construction of Spiro-Tetrahydroquinoline Skeleton - Liu, Hongmei; Quan, Yunyun; Xie, Long; Li, Xiang; Xie, Xin (Frontiers in Chemistry, 2022)
The direct functionalization of inert C–H bond is regarded as one of the most powerful strategies to form various chemical bonds and construct complex structures. Although significant advancements have been witnessed in the area of transition metal-catalyzed functionalization of inert C–H, several challenges such as the utilization and removal of expensive transition metal, limited capacity, poor atom economy, toxicity and et. al, can’t fully fulfil the high standard of modern green chemistry nowadays. Over the past decades, due to its inherent advantage comparing with transition metal-catalyzed strategy, the hydrogen transfer (HT) activation that applies “tert-amino effect” into the direct functionalization of the common and omnipresent C(sp3)–H bonds adjacent to tert-amines has attracted much attention from the chemists. In particular, the intramolecular [1,5]-HT activation, as the most common hydrogen transfer mode, enables the rapid and effective production of multifunctionally complex frameworks, especially the spiro-tetrahydroquinoline derivatives which are widely founded in biologically active natural products and pharmaceuticals. Although great accomplishments have been achieved in this promising field, rare review to date has systematically summarized these important progresses despite of scattered reports documented in several reviews. Hence, in this review we will summarize the significant advances in the cascade [1,5]-hydrogen transfer/intramolecular C(sp3)-H functionalization from the perspective of “tert-amino effect” to build spiro-tetrahydroquinoline skeleton, and the content is categorized by structure type of final spiro-tetrahydroquinoline products containing various pharmaceutical units. Besides, current limitations as well as future directions in this field are also pointed out. We hope our review could bring a quick look and provide some inspiration for the research of hydrogen transfer strategy in the future.